Assessment of hepatic fibrosis with non-invasive indices in subjects with diabetes before and after liver transplantation - Grancini, Valeria; Cogliati, Irene; Alicandro, Gianfranco; Gaglio, Alessia; Gatti, Stefano; Donato, Maria Francesca; Orsi, Emanuela; Resi, Veronica (Frontiers in Endocrinology, 2024)
Hepatogenous diabetes is a frequent complication of cirrhosis, and its prevalence increases with the severity of liver disease. In the post-transplant period, there are no data on the persistence of glucose metabolism alterations and the possible development of fibrosis in the transplanted organ. To this aim, we evaluated liver fibrosis in cirrhotic subjects both before and after liver transplantation. The study included 111 individuals who underwent liver transplantation and were reevaluated two years later to investigate the possible influence of the persistence of post-transplant diabetes in developing new fibrosis in the transplanted organ. The degree of fibrosis was assessed using the Fibrosis Index Based on 4 Factors Fibrosis-4 Score (FIB-4) and the Aspartate to Platelet Ratio Index (APRI). At pre-transplant evaluation, 63 out of 111 (56.8%) subjects were diabetic. Diabetic subjects had higher FIB-4 (Geometric mean, 95% confidence interval: 9. 74, 8.32-11.41 vs 5.93, 4.71-7.46, P<0.001) and APRI (2.04, 1.69-2.47 vs 1.18, 0.90-1.55, P<0.001) compared to non-diabetic subjects. Two years after transplantation, 39 out of 111 (35.1%) subjects remained with diabetes and continued to show significantly higher P<0.001) and APRI (0.52, 0.39-0.69 vs 0.26, 0.21-0.32, P<0.001) compared to people subjects without diabetes. Thus, the persistence of diabetes after transplantation exposes subjects to an increased risk of developing fibrosis in the newly transplanted organ, potentially leading to worsened longterm outcomes in this population.